ANALISIS KANDUNGAN ASAM RETINOAT PADA SEDIAAN KRIM MALAM YANG BEREDAR DI TOKO X KOTA KLATEN DENGAN SPEKTROFOTOMETRI UV-Vis - Anita Agustina Styawan; Choiril Hana Mustofa; Yenni Kusuma Wardhan (MOTORIK Jurnal Ilmu Kesehatan, 2020)
Whitening cosmetics are cosmetics that contain an active whitening ingredient to brighten the skin. Retinoic acid is prohibited from being used in whitening creams because it can cause dry, burning, carcinogenic and teratogenic skin. The purpose of this study was to determine the levels of retinoic acid contained in night creams. The sample in this study were 5 night cream products circulating in Klaten City X Store. This study was conducted to determine the content of retinoic acid in night creams using thin layer chromatography (TLC). Five positive samples contained retinoic acid by giving dark green spots and the concentration was determined by UV-Vis spectrophotometry. The results of this study indicate that in 5 samples of night cream circulating in Store X in the City of Klaten all positive for retinoic acid, that is, the average for sample A was 0.021%; sample B 0.014%; sample C 0.016%; sample D 0.025% and sample E 0.023%. Keywords: Retinoic Acid, Whitening Cream, UV-Vis Spectrophotometry